2003
DOI: 10.1001/jama.290.4.502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Dietary Portfolio of Cholesterol-Lowering Foods vs Lovastatin on Serum Lipids and C-Reactive Protein

Abstract: OST DIETARY MANIPULAtions result in modest cholesterol reductions of 4% to 13%, 1-10 and diet has been considered by some as a relatively ineffective therapy. 11 In contrast, 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (statins) repeatedly have been shown to reduce mean serum low-density lipoprotein cholesterol (LDL-C) concentrations by 28% to 35% in long-term trials, [12][13][14] with corresponding reductions in cardiovascular death of 23% to 32% in both primary and secondary prevention trials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
332
0
11

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 532 publications
(359 citation statements)
references
References 43 publications
16
332
0
11
Order By: Relevance
“…Dietary modification remains the preferred initial treatment option for improving major lipid risk factors rather than instigating drug therapy (NCEP, 2001;Anderson, 2003). Jenkins and coworkers recently proposed the 'Portfolio diet' as a new approach to lipid management: the diet utilizes a combination of hypocholesterolaemic agents such as psyllium, oats, nuts, plant sterols and soy protein to provide an additive effect in reducing total and low-density lipoprotein cholesterol (LDL-C), equivalent to first-line drug therapy (Jenkins et al, 2002a(Jenkins et al, , 2003. Dietary intervention studies have shown that numerous legumes (eg, soy beans, navy beans, field beans, lentils, chickpeas and pinto beans) beneficially modify serum lipids (Jenkins et al, 1983;Anderson et al, 1984Anderson et al, , 1990Anderson et al, , 1995Duane, 1997;Fruhbeck et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary modification remains the preferred initial treatment option for improving major lipid risk factors rather than instigating drug therapy (NCEP, 2001;Anderson, 2003). Jenkins and coworkers recently proposed the 'Portfolio diet' as a new approach to lipid management: the diet utilizes a combination of hypocholesterolaemic agents such as psyllium, oats, nuts, plant sterols and soy protein to provide an additive effect in reducing total and low-density lipoprotein cholesterol (LDL-C), equivalent to first-line drug therapy (Jenkins et al, 2002a(Jenkins et al, , 2003. Dietary intervention studies have shown that numerous legumes (eg, soy beans, navy beans, field beans, lentils, chickpeas and pinto beans) beneficially modify serum lipids (Jenkins et al, 1983;Anderson et al, 1984Anderson et al, , 1990Anderson et al, , 1995Duane, 1997;Fruhbeck et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…0% total energy and <50 mg dietary cholesterol/4 . 2 MJ (1000 kcal) was present (32)(33)(34) . Furthermore, the diet provided 30 .…”
Section: The Dietary Portfoliomentioning
confidence: 99%
“…05). These two approaches were shown to be more effective in modifying the risk factors of CHD than the NCEP-derived control (33) .…”
Section: The Dietary Portfolio: Metabolic Trialsmentioning
confidence: 99%
See 2 more Smart Citations